Scaling-Up a Community-Driven HIV/AIDS Program in Malawi - Kadiyala, Suneetha (World Bank, Washington, DC, 2012)
This note is part of a series that examines factors that facilitate the scaling up of Community Driven Development (CDD) programs. The note describes the factors that enabled and constrained the scaling up of a community based HIV/AIDS intervention in Malawi - Scaling-up HIV/AIDS Interventions through Expanded Partnerships (STEPs). The STEPs initiative assists local HIV/AIDS committees with community mobilization and capacity building so that communities become empowered to act collectively to address their own problems.